Muscle Response to Complete Peripheral Nerve Injury: Changes of Acetylcholine Receptor and Creatine Kinase Activity over Time - Rochkind, Shimon; Shainberg, Asher (Journal of Reconstructive Microsurgery, 2017)
Background This study was designed to assess the changes of acetylcholine receptor (AChR) and creatine kinase (CK) levels, which are important biochemical markers for muscle viability in cases of long-term muscle denervation. Scientists and peripheral nerve surgeons may find these data important regarding maximal range of muscle viability applicable for timing of effective peripheral nerve reconstructive surgery.Methods The study was conducted on 48 rats (96 gastrocnemius muscles), whose right legs were denervated by removing a 10-mm segment of sciatic nerve, while their left legs remained intact. Under general anesthesia, the rats were euthanized at seven points in time, on days 7, 14, 21, 30, 60, 120, and 210. In both legs, AChR was quantified by 125I-α-bungarotoxin, whereas CK activity was measured using a spectrophotometric method.Results CK levels in the denervated limb reached a minimal level of 34% on day 30 in comparison to the intact limb and remained at this level up to 210 days after operation. AChR levels in the denervated limb reached a minimal level of 38% on day 120 in comparison to the intact limb and remained at this level up to 210 days after operation.Conclusion The present study shows that AChR and CK levels in rat denervated muscles remain constant at about third of its intact condition for a period of at least a third of rat's lifetime postinjury.
Keywords: muscle denervation; acetylcholine receptors; creatine kinase